2020
DOI: 10.1177/8756972819896113
|View full text |Cite
|
Sign up to set email alerts
|

What Are the Causes and Cures of Poor Megaproject Performance? A Systematic Literature Review and Research Agenda

Abstract: This systematic literature review explores the megaproject management literature and contributes by improving our understanding of the causes and cures of poor megaproject performance. The review analyzes 6,007 titles and abstracts and 86 full papers, identifying a total of 18 causes and 54 cures to address poor megaproject performance. We suggest five avenues for future research that should consider examining megaprojects as large-scale, inter-organizational production systems: (1) designing the syst… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
95
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 159 publications
(124 citation statements)
references
References 133 publications
(193 reference statements)
0
95
0
Order By: Relevance
“…Atkinson (1999) advocated the need for considering additional project performance criteria besides cost, quality, and time such that long-term benefits to the organization and stakeholders could be exclusively captured. This conceptualization of project performance could justify the rationale behind undertaking complex projects and embracing complexity, because although complex projects generally result in cost and time overruns (Denicol et al, 2020; Williams, 2017), the strategic importance of such projects outweighs other conventional performance criteria. In this article, we adopt this notion of embracing a wide range of performance dimensions and conceptualize project performance as the overall performance of a project encompassing both short-term and long-term performance criteria.…”
Section: Introductionmentioning
confidence: 99%
“…Atkinson (1999) advocated the need for considering additional project performance criteria besides cost, quality, and time such that long-term benefits to the organization and stakeholders could be exclusively captured. This conceptualization of project performance could justify the rationale behind undertaking complex projects and embracing complexity, because although complex projects generally result in cost and time overruns (Denicol et al, 2020; Williams, 2017), the strategic importance of such projects outweighs other conventional performance criteria. In this article, we adopt this notion of embracing a wide range of performance dimensions and conceptualize project performance as the overall performance of a project encompassing both short-term and long-term performance criteria.…”
Section: Introductionmentioning
confidence: 99%
“…Bounded rationality is often cited in project studies as a causal mechanism of poor infrastructure project performance [19]. Causal mechanisms are a central element of our study and refer to "a constellation of entities and activities that are organized such that they regularly bring about a particular type of outcome, and we explain an observed outcome by referring to the mechanism by which such outcomes are regularly brought about."…”
Section: Real Options Reasoning In Complex Projectsmentioning
confidence: 96%
“…Our study offers four broad theoretical implications related to ROR. First, prior to our study, there have been few attempts to formulate perspectives that allow the simultaneous study of multiple causes of an inadequate development process [19], [28], [62]. In addition, few studies have shown that decision-makers apply the logic of real options in project settings [4], [16], [43].…”
Section: Theoretical Implicationsmentioning
confidence: 99%
“…Despite an increasing volume of works, megaprojects still seem to underperform. Denicol, Davies and Krystallis (2020) in their review of megaproject literature maps 54 different cures corresponding to 18 causes of poor performance. The poor performance of these projects after the presence of the cures within the literature shows the gap between knowing and doing.…”
Section: Knowing-doing Gapmentioning
confidence: 99%